2020
DOI: 10.1038/s42003-020-0847-y
|View full text |Cite
|
Sign up to set email alerts
|

The COX-2/PGE2 pathway suppresses apical elimination of RasV12-transformed cells from epithelia

Abstract: At the initial stage of carcinogenesis, when RasV12-transformed cells are surrounded by normal epithelial cells, RasV12 cells are apically extruded from epithelia through cell competition with the surrounding normal cells. In this study, we demonstrate that expression of cyclooxygenase (COX)−2 is upregulated in normal cells surrounding RasV12-transformed cells. Addition of COX inhibitor or COX-2-knockout promotes apical extrusion of RasV12 cells. Furthermore, production of Prostaglandin (PG) E 2 , a downstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“… 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Retention of excess, mutant, or aberrant cells would impair tissue integrity and promote disease. 11 , 12 , 13 The mechanisms underlying these processes are multifaceted and involve cell competition, 14 mechanical cues, 15 and cell plasticity. 16 Epithelial cells expressing oncogenes compete for space and survival in tissues and are often eliminated via processes that require the presence of normal cells; however, the mechanisms underlying how normal cells sense and eliminate mutant cells remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Retention of excess, mutant, or aberrant cells would impair tissue integrity and promote disease. 11 , 12 , 13 The mechanisms underlying these processes are multifaceted and involve cell competition, 14 mechanical cues, 15 and cell plasticity. 16 Epithelial cells expressing oncogenes compete for space and survival in tissues and are often eliminated via processes that require the presence of normal cells; however, the mechanisms underlying how normal cells sense and eliminate mutant cells remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48][49] Recent studies have demonstrated that several environmental factors can affect the occurrence of cell competition, such as obesity, inflammation, and calorie restriction. 19,20,50 Here, we demonstrate that sequential oncogenic mutations can also influence the cell competition phenotype. Under the wild-type background, newly emerging RasV12-transformed cells are often eliminated from epithelia.…”
Section: Discussionmentioning
confidence: 70%
“…18 However, the strength of EDAC varies, depending on epithelial tissues, and multiple environmental factors, such as inflammation and obesity, would diminish EDAC; under these environmental conditions, a certain fraction of transformed cells remains within epithelia and forms potentially precancerous lesions. 19,20 Indeed, recent studies using next-generation sequencing have revealed that, in the human adult body, there exist clonally expanded cells with a single oncogenic mutation. [21][22][23][24] However, it remains enigmatic whether and how these lesions eventually develop into malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…COX-2 is a constitutively expressed protein, which imparts a significant role as another key mediator in inflammation. COX-2 reportedly converts arachidonic acid to prostaglandin (PG), dilating blood vessels and enhancing microvascular permeability ( Sato et al, 2020 , Nakanishi and Rosenberg, 2013 ). Activator protein-1 (AP-1) is another prominent transcription factor involved in generating inflammatory responses ( Raivich and Behrens, 2006 , Renoux et al, 2020 ) and its active phosphorylated form has been reported to support the enhanced expression of inflammatory cytokines ( Kawai and Akira, 2007 ).…”
Section: Introductionmentioning
confidence: 99%